Evaluation of bone regenerative and bioactive potential of β-TCP/PLLA/PGA nanobiomaterial in conjunction with concentrated conditioned media from rapidly expanding clone (REC) of mesenchymal stem cells: A pilot animal study - Ankhtsetseg Shijirbold; Mrunalini Ramanathan; Masako Fujioka-Kobayashi; Nithish Sankepally; Yuhei Matsuda; Yumi Matsuzaki; Yuki Fujita; Takahiro Kanno (PLoS ONE, 2025)
Maxillofacial bone defects present substantial challenges in reconstruction because of their impact on function and aesthetics. Mesenchymal stem cells (MSCs) have been used for therapeutic purposes; however, various technical issues limit their application. A variant of MSCs called “rapidly expanding clone” (REC) was introduced using the superselection method. Conditioned media (CM) from stem cells have shown promising regenerative efficacy and can prevent host immunogenic reactions. We hypothesized that the bone regeneration potential of β-TCP/PLLA/PGA nanobiomaterial scaffold combined with concentrated CM-derived REC MSCs could enhance the regeneration process. For comparative evaluation, plain CM, 1 time concentrated REC-CM (1 × REC-CM), and 10 times concentrated REC-CM (10 × REC-CM) subgroups were generated. The quantity of growth factors in each CM group was assessed using enzyme-linked immunosorbent assay. β-TCP/PLLA/PGA scaffold implantation with REC-CM was performed in rats with critical-sized mandibular defects. Newly regenerated bone was evaluated using the bone volume-to-total volume (BV/TV) ratio, bone mineral density (BMD), and defect margin regrowth, and bioactivity was checked for Runx2, LepR, osteocalcin, periostin accumulation, and deposition at weeks 1 and 4. 10 × REC-CM promoted angiogenesis by significantly elevating TGF-β1 (p = 0.0002) and VEGF (p = 0.007) levels, facilitating vascularization and matrix deposition. The 10 × REC-CM group demonstrated substantially higher BV/TV at week 4 and new bone regeneration in the inner defect region at both time points (p = 0.002; p = 0.04) than the other groups. Significant elevation in the levels of osteogenic markers, such as Runx2 (p = 0.001; p = 0.05), LepR (p = 0.002; p = 0.001), osteocalcin (p = 0.001), and periostin, was observed in the 10 × REC-CM group, indicating good osteoinductivity. These findings highlight the synergistic effect of β-TCP/PLLA/PGA scaffold and REC-CM in promoting effective bone regeneration. The therapeutic potential of REC-CM-enhanced scaffolds in maxillofacial and bone reconstruction is supported by the findings presented in this study. This study demonstrates the upregulation and early phase bone regeneration upon application of 10x REC-CM with β-TCP/PLLA/PGA nanobiomaterial.